Microalgae as a Source of Bioenergy: Products, Processes and Economics - Carlos Magalhães Pires, José (Bentham Science Publishers, 2017)
Microalgae could play an important role in the achievement of sustainability goals related to the generation of renewable energy and greenhouse gas (GHG) emissions. These photosynthetic microorganisms are able to capture CO2 and, therefore, can be used to produce biofuels such as ethanol, methane and green diesel. Other factors, such as their high growth rate, ability to use wastewater as a culture medium and the ability to grow on non-arable land makes them a potentially economical source of biofuel production on a large scale.This monograph introduces the reader to the basic and applied science of microalgal biofuel production. Chapters in the volume give information about bioethanol and biogas production from microalgal sources, the fermentation process, optimization of culture parameters and industrial applications of biomass projects.The book is a useful reference for biotechnology and environmental science graduates and professionals interested in biofuel production.